Multidisciplinarity in law research (Docentes 2.0 Journal, 2013)
As a methodological tool, Multidisciplinarity (also called "Multidisciplinarity") in the investigation of law consists in observing the same legal phenomenon from the perspective of many disciplines, thus, a legal institution, e.g. economic competition can be analyzed from the entirely legal perspective (following the example) as an individual guarantee, or, from the perspective of economic science as a motivation for investment.
Keywords: Multidisciplinarity; law research